(untitled) - Bryla, Bob (San Francisco, Calif.,London, 2003)
Oracle9i DBA JumpStart gives you the solid grounding you need to approach Oracle certification with confidence: Introduction to relational database concepts Using basic SQL*Plus and iSQL*Plus commands Understanding Oracle database functions Using multiple tables Restricting, sorting, and grouping data Creating and maintaining a database Using SQL*Plus reporting techniques Creating and maintaining database objects Setting up users and managing security Configuring optimization Creating backups Troubleshooting
Keywords: Relational databases,Database management,Cơ sở dữ liệu quan hệ,Quản lý cơ sở dữ liệu